Pengaruh Kualitas Produk dan Harga Terhadap Kepuasan Dan Loyalitas Konsumen pada Hand and Body Lotion Vaseline - Nisa', Dina Auliya; Andriani, Nurita (Jurnal Kajian Ilmu Manajemen (JKIM), 2025)
The increasing number of people's desires and needs for beauty products has led companies to create products with good quality and affordable prices. This research aims to analyze the influence of product quality and price on consumer satisfaction and loyalty of Vaseline hand and body lotion. The research method used is quantitative. The respondents of this research were students from the Faculty of Economics and Business, Trunojoyo Madura University who had purchased and used at least 2 times in the last 3 months Vaseline hand and body lotion with a sample size of 97. The results of this research show that the product quality variable and the price variable have a positive and significant effect on consumer satisfaction. Product quality does not have a positive and significant effect on consumer loyalty, but the price variable has a positive and significant effect on consumer loyalty. The product quality variable and the variables have a positive and significant effect on consumer loyalty through satisfaction. The findings from this research indicate that companies must continue to maintain the quality of their products and be able to increase the variety of vaseline hand and body lotion products and still be able to provide affordable prices for their consumers in order to maintain consumer satisfaction and loyalty.